2012
DOI: 10.1128/jb.01296-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Pseudomonas luteola XLDN4-9 and Pseudomonas stutzeri XLDN-R, Two Efficient Carbazole-Degrading Strains

Abstract: Pseudomonas luteola XLDN4-9 and Pseudomonas stutzeri XLDN-R are two efficient carbazole-degrading pseudomonad strains. Here we present 4.63-and 4.70-Mb assemblies of their genomes. Their annotated key genes for carbazole catabolism are similar, which may provide further insights into the molecular mechanism of carbazole degradation in Pseudomonas. Carbazole and its derivatives in N-heterocyclic compounds have a dioxin-like structure, and some of them are toxic and mutagenic (5). They are most common in creosot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…fluorescens, putida, alcaligenes ) have been reported to degrade the fatty acid derivatives, its implicit presence in RL indicates at its differential capacity to use α-linoleic acid as carbon source [ 75 ]. Similarly, when compared to the other genomes (n = 17), P. stutzeri XLDN-R was found to exclusively possess the carbazole degradation pathway which was further supported by the fact that this particular strain was isolated from soil for its differential ability to utilize carbazole as sole source of both carbon and nitrogen [ 69 ]. 3-chloroacrylic acid degradation pathway was found uniquely in P. stutzeri CCUG 29243 indicating at its capability of using 3-chloroacrylic acid as carbon source [ 76 ].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…fluorescens, putida, alcaligenes ) have been reported to degrade the fatty acid derivatives, its implicit presence in RL indicates at its differential capacity to use α-linoleic acid as carbon source [ 75 ]. Similarly, when compared to the other genomes (n = 17), P. stutzeri XLDN-R was found to exclusively possess the carbazole degradation pathway which was further supported by the fact that this particular strain was isolated from soil for its differential ability to utilize carbazole as sole source of both carbon and nitrogen [ 69 ]. 3-chloroacrylic acid degradation pathway was found uniquely in P. stutzeri CCUG 29243 indicating at its capability of using 3-chloroacrylic acid as carbon source [ 76 ].…”
Section: Resultsmentioning
confidence: 96%
“…However, two sub-groups were identified for P. stutzeri clade, first with P. stutzeri CCUG 29243 and ATCC 14405, and second containing P. stutzeri A1501, T13 and XLDN-R (Figure 1 A). This distinct deviation could be accredited to the ecotype status resulting from the niche specific adaptations, as P. stutzeri ATCC 14405 and CCUG 29243 both are marine isolates [ 66 , 67 ] however, A1501, T13, and XLDN-R, are well-known soil/sludge dwellers [ 68 , 69 ]. ANI values for P. stutzeri group (≤88.2%) were also not in accordance with species demarcation value of 95-96% [ 65 ] indicating towards intra species level divergence (Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…The coding sequences were classified into 2,965 subsystems, the most abundant of which were metabolism of amino acids derivatives ( n = 314 CDSs) and carbohydrates ( n = 273); cofactors, vitamins, prosthetic groups, and pigments ( n = 258); and protein metabolism ( n = 250). A comparison of genome sequences available in the RAST data sets revealed that P. stutzeri A1501 ( 11 ) is the closest neighbor of the KF716 strain with a score of 534, followed by P. stuzeri XLDN-R with a score of 462 ( 12 ). The bph-sal element, similar to that of P. putida KF715 identified previously ( 2 ), was found in a single contig.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Genome assemblies for ten strains of P. stutzeri , including one type strain (clinic CGMCC 1.1803 [3]), one naphthalene-degrading strain (CCUG 29243 [4]), two nitrogen-fixing strains (A1501 [5], DSM 4166 [6]), one carbazole-degrading (XLDN-R [7]), one arsenite-oxidizing strain (TS44 [8]), some model strains (denitrification CCUG 16156 [9], T13 [10]), a natural transformation strain (DSM 10701 [11]), and a lactate utilization strain (SDM-LAC [12]), are already available at GenBank. We used them for comparison with the genome of strain KOS6.…”
Section: Genome Announcementmentioning
confidence: 99%